Trade Determinants and Potential of Syria : Using a Gravity Model ‘With an Estimation of the Syrian Crisis’ Impact on Exports’ - Mehchy, Zaki; Nasser, Rabie; Schiffbauer, Marc (Taylor and Francis, 2015)
This paper diagnoses export determinants for Syria between 1995 and 2010 using a gravity model applying Heckman's two-step approach with Least Squares Dummy Variables. The model analyzes total and manufacturing exports separately. In addition to the standard explanatory variables, the gravity model is augmented with the nominal effective exchange rate and institutional performance variables. The results show the importance of a relative improvement in Syrian institutions to increase exports. Furthermore, the paper estimates an index that identifies countries with a high potential demand for Syrian products. Finally, the gravity model is used to simulate the impact of the ongoing conflict in Syria on the potential for exports; the results show that sanctions and the deterioration in institutional factors are expected to have reduced Syria's export potential by more than 70%, which might lead to a complete collapse of the economy in the short term.